Arabic Folklore The Termite of Prophet Sulayman (Solomon) & The Jinn Race (Demon) - Vandestra, Muhammad (Scribl, 2018)
{Then when We decreed death for him [Sulayman (Solomon)], nothing informed them (Jinn) of his death except a termite, which kept (slowly) gnawing away at his stick, so when he fell down, the Jinn saw clearly that if they had known the Ghayb (unseen), they would not have stayed in the humiliating torment.} (Saba': 14) Let me tell you what happened. While we were just tiny ants that live in ou ...